2020
DOI: 10.3390/app10113924
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Elastic Wave Energy Imaging for the Detection and Localization of In-Sight and Out-of-Sight Defects in Composites

Abstract: In this study, both linear and nonlinear vibrational defect imaging is performed for a cross-ply carbon fiber-reinforced polymer (CFRP) plate with artificial delaminations and for a quasi-isotropic CFRP with delaminations at the edge. The measured broadband chirp vibrational response is decomposed into different components: the linear response and the nonlinear response in terms of the higher harmonics. This decomposition is performed using the short-time Fourier transformation combined with bandpass filtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In addition, the plate with BVID is covered with removable reflective tape (3M™ Scotchlite™ 680CRE10). This was required to be able to detect the nonlinear vibrational components which are of low J o u r n a l P r e -p r o o f amplitude [23,37,38]. In both cases, the propagation of the fundamental anti-symmetric Lamb mode (A 0 ), which has a dominant out-of-plane surface velocity response, is investigated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the plate with BVID is covered with removable reflective tape (3M™ Scotchlite™ 680CRE10). This was required to be able to detect the nonlinear vibrational components which are of low J o u r n a l P r e -p r o o f amplitude [23,37,38]. In both cases, the propagation of the fundamental anti-symmetric Lamb mode (A 0 ), which has a dominant out-of-plane surface velocity response, is investigated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…One speaks about nonlinear elastic wave spectroscopy (NEWS) [24][25][26][27][28][29][30] or nonlinear elastic wave modulation spectroscopy (NEWMS) [31][32][33][34][35][36], when there is a single excitation or when there are multiple excitation signals, respectively. Very recently, the current authors used J o u r n a l P r e -p r o o f (numerical as well as experimental) NEWS to show that the nonlinear response at the defect can be used for the detection of shallow damages and, more important, deep backside delaminations [37,38]. It was observed that defects act as secondary sources of higher harmonic vibrational components which can be measured at a distance from the defect's location.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of the current authors [38], it was illustrated how the short-time Fourier transform (STFT) and specific bandpass windows in the time-frequency domain can be used to extract higher harmonic components from broadband measurement data. Here, the same technique is used with the difference that there is a second sine excitation source present.…”
Section: Nonlinear Component Extractionmentioning
confidence: 99%
“…As such, it is beneficial to match the excitation frequency with a frequency for which efficient energy trapping, or better LDR, occurs [11]. When a single source of vibrations is employed, the nonlinear elastic wave spectroscopy (NEWS) shows promising results in revealing the defect as a source of higher harmonic components [31][32][33][34][35][36][37][38][39]. Current authors showed that a backside delamination (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear analysis methods have gained popularity in the theoretical and applied research focusing on nonclassical nonlinear behaviour of interfaces (referred to as local nonlinearities) [33][34]. Recent studies have primarily focused on the investigation of higher harmonic generation due to the J o u r n a l P r e -p r o o f presence of nonlinear-elasticity [28,35] and contact-nonlinearity [36][37] phenomena. A contact acoustic nonlinearity model of a closed crack in an aluminium plate was developed for the analysis of nonlinear characteristics of the crack induced elastic waves in the structure [38].…”
Section: Introductionmentioning
confidence: 99%